Sulfonylurea-responsive neonatal diabetes mellitus diagnosed through molecular genetics in two children and in one adult after a long period of insulin treatment - Fanciullo, L.; Iovane, B.; Gkliati, et al., D. (Acta Biomedica Atenei Parmensis, 2012)
A permanent neonatal diabetes mellitus has finally been diagnosed through molecular genetics in two children and one adult after 9 to 35 years of uninterrupted insulin treatment. These patients developed diabetes before 6 months of age and were autoantibody negative. In one boy, a mutation in the KCNJ11 gene was identified at 9 years of age. In the other two patients (daughter and father, 12.6 and 25 years old respectively) the new gene variant (ABCC8/L213P) was found. Switching from insulin to sulfonylurea treatment leads to the definitive discontinuance of insulin therapy, improving metabolic control as well as the amelioration of the associated neurodevelopmental disabilities in the young girl in which an intermediate Development Delay, Epilepsy, Neonatal Diabetes syndrome was diagnosed.